Transgene‐mediated skeletal phenotypic variation in zebrafish - Charles B. Kimmel; Alexander L. Wind; Whitney Oliva; Samuel D. Ahlquist; Charline Walker; John Dowd; Bernardo Blanco‐Sánchez; Tom A. Titus; Peter Batzel; Jared C. Talbot; John H. Postlethwait; James T. Nichols (Journal of Fish Biology, 2021)
When considering relationships between genotype and phenotype we frequently ignore the fact that the genome of a typical animal, notably including that of a fish and a human, harbours a huge amount of foreign DNA. Such DNA, in the form of transposable elements, can affect genome function in a major way, and transgene biology needs to be included in our understanding of the genome. Here we examine an unexpected phenotypic effect of the chromosomally integrated transgene fli1a‐F‐hsp70l:Gal4VP16 that serves as a model for transgene function generally. We examine larval fras1 mutant zebrafish ( Danio rerio ). Gal4VP16 is a potent transcriptional activator that is already well known for toxicity and mediating unusual transcriptional effects. In the presence of the transgene, phenotypes in the neural crest‐derived craniofacial skeleton, notably fusions and shape changes associated with loss of function fras1 mutations, are made more severe, as we quantify by scoring phenotypic penetrance, the fraction of mutants expressing the trait. A very interesting feature is that the enhancements are highly specific for fras1 mutant phenotypes, occurring in the apparent absence of more widespread changes. Except for the features due to the fras1 mutation, the transgene‐bearing larvae appear generally healthy and to be developing normally. The transgene behaves as a genetic partial dominant: a single copy is sufficient for the enhancements, yet, for some traits, two copies may exert a stronger effect. We made new strains bearing independent insertions of the fli1a‐F‐hsp70l:Gal4VP16 transgene in new locations in the genome, and observed increased severities of the same phenotypes as observed for the original insertion. This finding suggests that sequences within the transgene, for example Gal4VP16, are responsible for the enhancements, rather than the effect on neighbouring host sequences (such as an insertional mutation). The specificity and biological action underlying the traits are subjects of considerable interest for further investigation, as we discuss. Our findings show that work with transgenes needs to be undertaken with caution and attention to detail.

Maximizing information from space data resources: a case for expanding integration across research disciplines - Nandu Goswami; Jerry J. Batzel; Gilles Clément; T. Peter Stein; Alan R. Hargens; M. Keith Sharp; Andrew P. Blaber; Peter G. Roma; Helmut G. Hinghofer-Szalkay (European Journal of Applied Physiology, 2013)